2005
DOI: 10.1530/eje.1.01889
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide mediates abnormal responsiveness of thyroid arteries in methimazole-treated patients

Abstract: Objective: We studied the intervention of nitric oxide (NO), prostacyclin and endothelium-derived hyperpolarizing factor (EDHF) in mediating responses to acetylcholine in thyroid arteries from euthyroid and methimazole-treated (MT) patients. Design and methods: Branches of the superior thyroid artery were obtained from 19 euthyroid patients and 17 MT patients (euthyroid at the time of surgery) undergoing total thyroidectomy or hemithyroidectomy. Artery rings were suspended in organ baths for isometric recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
7
1
1
Order By: Relevance
“…This study demonstrated that endothelium‐dependent FMD was greater in hyperthyroid patients than in controls. In agreement with human studies, forearm blood flow and relaxation of thyroid arteries in response to acetylcholine are increased in hyperthyroid patients 23,24 . However, findings obtained in this study are in conflict with a human study showing that the FMD values decreased in subclinical hypothyroidism or hyperthyroidism 25 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This study demonstrated that endothelium‐dependent FMD was greater in hyperthyroid patients than in controls. In agreement with human studies, forearm blood flow and relaxation of thyroid arteries in response to acetylcholine are increased in hyperthyroid patients 23,24 . However, findings obtained in this study are in conflict with a human study showing that the FMD values decreased in subclinical hypothyroidism or hyperthyroidism 25 .…”
Section: Discussionsupporting
confidence: 69%
“…The vascular segments of hyperthyroid rodents relaxation in response to acethylcholine were decreased or unchanged in some studies, 18–21 whereas other studies reported that these animals had increased relaxation responding to acetylcholine 4–9 . Reports regarding vascular response in patients with hyperthyroidism are limited 23,24 . This is the first study using FMD as a noninvasive indicator of vascular endothelial function to evaluate hyperthyroid patients during the hyperthyroid state and their euthyroid state following treatment with antithyroid agents.…”
Section: Discussionmentioning
confidence: 95%
“…[2526] Partial restoration of FMD when treating hyperthyroid patients may be due to increase of endothelium-derived hyperpolarizing factor in hyperthyroid patients, which cannot be corrected by treatment. [27] In our study, we illustrate that FMD changes are not related to hypothyroidism background because after reduce dose of levothyroxine, FMD became better than past.…”
Section: Discussionmentioning
confidence: 64%
“…Such data might be of pathophysiological significance in those states characterised by increased plasma vasopressin levels, such as haemorrhagic and septic shock (Landry et al, 1997;Tsuneyoshi et al, 2003) and in some patients with congestive heart failure (Rouleau et al, 1994;Goldsmith and Gheorghiade, 2005). Studies from our laboratory have shown that in human thyroid arteries from multiorgan donors the endothelium modulates responses to acetylcholine and noradrenaline through the release of nitric oxide (NO), an endothelium-derived relaxing factor (Torondel et al, 2004;Ortega et al, 2005). Moreover, NO production is decreased in hyperthyroid patients when compared with control subjects (Hermenegildo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%